Sampling the diurnal and annual cycles of the Earth's energy imbalance with constellations of satellite-borne radiometers - T. Hocking; T. Hocking; T. Mauritsen; T. Mauritsen; L. Megner; L. Megner (Atmospheric Measurement Techniques)
The Earth's energy imbalance, i.e. the difference between incoming solar radiation and outgoing reflected and emitted radiation, is the one quantity that ultimately controls the evolution of our climate system. However, despite its importance, there is limited knowledge of the exact magnitude of the energy imbalance, and the small net difference of about 1 W m−2 between two large fluxes (approximately 340 W m−2) makes it challenging to measure directly. There has recently been renewed interest in using wide-field-of-view radiometers on board satellites to measure the outgoing radiation, as a possible method for deducing the global annual mean energy imbalance. Here we investigate how to sample in order to correctly determine the global annual mean imbalance and interannual trends, using a limited number of satellites. We simulate satellites in polar (90° inclination), sun-synchronous (98°) and precessing orbits (73, 82°), as well as constellations of these types of satellite orbits. We find that no single satellite provides sufficient sampling, both globally and of the diurnal and annual cycles, to reliably determine the global annual mean. If sun-synchronous satellites are used, at least six satellites are required for an uncertainty below 1 W m−2. One precessing satellite combined with one polar satellite results in root-mean-square errors of 0.08 to 0.10 W m−2, and a combination of two or three polar satellites results in root-mean-square errors of 0.10 or 0.04 W m−2, respectively. In conclusion, at least two satellites that complement each other are necessary to ensure global coverage and achieve a sampling uncertainty well below the current estimate of the energy imbalance.